2019
DOI: 10.3390/ijerph16061085
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Inflammatory Responses in Human Bronchial Epithelial Cells Induced by Spores and Hyphal Fragments of Common Damp Indoor Molds

Abstract: Damp indoor environments contaminated with different mold species may contribute to the development and exacerbation of respiratory illnesses. Human bronchial epithelial BEAS-2B cells were exposed to X-ray treated spores and hyphal fragments from pure cultures of Aspergillus fumigatus, Penicillum chrysogenum, Aspergillus versicolor and Stachybotrys chartarum. Hyphal fragments of A. fumigatus and P. chrysogenum induced expression and release of the pro-inflammatory cytokine interleukin (IL)-6 and the chemokine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 58 publications
0
31
0
1
Order By: Relevance
“…These cells can differentiate into squamous cells in response to certain substances, which make them amenable for screening chemicals that may induce or affect cell differentiation processes potentially relevant to carcinogenesis [55]. Studies using BEAS-2B cells have identified alterations in cell differentiation signaling in response to PM 2.5 [56], indoor molds [57], and diesel exhaust particles [58].…”
Section: Cell Modelsmentioning
confidence: 99%
“…These cells can differentiate into squamous cells in response to certain substances, which make them amenable for screening chemicals that may induce or affect cell differentiation processes potentially relevant to carcinogenesis [55]. Studies using BEAS-2B cells have identified alterations in cell differentiation signaling in response to PM 2.5 [56], indoor molds [57], and diesel exhaust particles [58].…”
Section: Cell Modelsmentioning
confidence: 99%
“…Using a silencing method, it has been demonstrated that TLR2, in a heterodimer form with TLR1 or TLR6, is required for the expression of Dectin-1 by HBE cells in response to A. fumigatus infection (29). Moreover, blocking TLR2 with antibodies results in the inhibition of the release of IL-6 and IL-8 by BEAS-2B cells infected with A. fumigatus hyphal fragments (59). Certain polymorphisms in TLR4, receptor for the bacterial lipopolysaccharide, are clearly associated with increased susceptibility to invasive aspergillosis (60).…”
Section: Recognition Of Aspergillus Fumigatus By Bronchial Epithelialmentioning
confidence: 99%
“…TLR4 expressed by mouse macrophages, recognizes A. fumigatus conidia and hyphae and induces the release of pro-inflammatory molecules. However, after blocking TLR4 with a specific monoclonal antibody, Øya et al failed to detect any significant change in the levels of IL-6 and IL-8 released by BEAS-2B cells infected with X-ray-treated hyphal fragments of A. fumigatus (59). Hypomethylated DNA, the natural ligand of TLR9, has been extracted in A. fumigatus hyphae (61).…”
Section: Recognition Of Aspergillus Fumigatus By Bronchial Epithelialmentioning
confidence: 99%
“…Actually, the inflammatory potential of A fumigatus hyphal fragments was higher than the two less pathogenic species tested. In strong contrast to A fumigatus , spores of P chrysogenum germinated poorly in vitro . A mouse study found that resting A fumigatus spores formed germ tubes in the lung tissue rapidly after inhalation, whereas no signs of germination of A versicolor spores were seen .…”
Section: Characterization and Pro‐inflammatory Potential Of Mold Partmentioning
confidence: 99%